“Human rights” in dispute: State violence and demands for justice in a comparative perspective - Lucia Eilbaum (Oñati International Institute for the Sociology of Law, 2021)
This paper proposes a reflection on the “human rights” category, as a native category, endowed with local and specific meanings. Therefore, it utilizes a comparative perspective by contrast on the uses and meanings of the “state violence” category and the building of processes demanding justice in Rio de Janeiro, in comparison to Buenos Aires. Specifically, it focuses on the ethnography produced after the murder of Rio's alderwoman Marielle Franco, to propose the notion of “attack on human rights”, showing how the category has been built through an antagonistic logic in Rio de Janeiro.